A Computable General Equilibrium Analysis of Fishery Management in a Small Honduran Community - Pouliot, Frédéric (Université d'Ottawa | University of Ottawa, 2019)
Open access exploitation of a natural resource has been shown to completely dissipate rents. This is particularly problematic for small economies who rely heavily on natural resources for their livelihood. We study the case of a small Honduran community with an open access fishery. We construct a multi-sector general equilibrium model of the economy with mobile factors. We then simulate management policies on the fishery and analyze their economy-wide consequences. This paper, at its core, is an extension of the work of Dale T. Manning, J. Edward Taylor and James E. Wilen in ‘General Equilibrium Tragedy of the Commons’.